Pengalaman Perawat dalam Melaksanakan Asuhan Keperawatan dengan Metode Tim di Ruang Rawat Inap RSUD dr. Slamet Garut - Iwan Wahyudi; Yayang Yusti Sintya (Jurnal Medika Cendikia, 2017)
Methods of nursing care nursing services in the field. Methods of nursing care need consideration for conformity in the method of implementation in health care institutions which supported by some methods. Team method is the provision of nursing care which is led by a group the team responsible of team, the person in charge of the team who holdimg the patient with his team. The researcher's problem is how the experience of nurse’s intervetion with team method in the patient ward of RSUD dr. slamet garut with qualitative approach to phenomenology. The purpose of this study is to express the experience which is more profound about the experience of nurse’s intervetion with team method in the patient ward of RSUD dr. Slamet Garut. Data collection technique through in-depth interviews and participatory observation, with three informants selected by purposive. data collected in the from of recording interviews and analyzed by Collaizi method. This study identified four themes: 1) Ineffective use of team methods, 2) Implementation of the activities of team methods in the room, 3) Advantages gained during running team methods in the room, 4) Barriers to implementation in team methods. The results showed that the three informants did not understand the implementation of the team method, the minimal resources because the number of nurses is still less than the needs of the room, the legality of the use of unofficial mrthods, not walking implementation of pre confrence post confrence and round.